Wh-Argument/Adjunct Asymmetry in Sentence Processing - Taylan Akal (Dilbilim Araştırmaları Dergisi, 2017)
This study investigates the processing of complex sentences with wh-phrases trying to point out whether the proposals stating that arguments are processed easier than adjuncts work for wh-phrases in case of Turkish. A wh-argument and a wh-adjunct were used in two eye-tracking experiments with two word orders, and two embedded verb types as the variables. The orders and the type of the embedded verbs were the same in each experiment to provide the wh-phrase type to be the main variable to compare. The general outcome of the study showed that wh-argument was processed more quickly than wh-adjunct supporting the diversification proposed by both formal and experimental approaches in terms of argument adjunct distinction. In a particular condition, in which the subcategorization features of the embedded verb mismatched with the number of arguments, the processing of wh-adjunct was faster than wh-argument. This seems to support a verb-oriented approach in licensing the scrambled wh-phrases.